Probiotic fermented Carica papaya water kefir with chemopreventive potential - Chin, Kah Wei; Khoo, Shing Ching; Luang-In, Vijitra; Tan, Suat Hian; Ma, Nyuk Ling (Elsevier, 2025)
Growing interest in functional foods has led to innovative approaches for cancer prevention and treatment. Probiotic-fermented foods shows promise in modulating gut microbiota and promoting health. This study optimized the fermentation process of probiotic Carica papaya water kefir (PWK) and evaluated its antibacterial and cytotoxic effects on MCF-7 and HCT116 cancer cells, 3T3-L1 and L6 normal cells. The optimal PWK formulation was prepared at 25 ◦C using probiotic consortium (Enterobacter xiangfangensis 4 A–2A3.1, Lactiplantibacillus plantarum SK321, Limosilactobacillus fermentum SK324, Lactococcus hircilactis WS16, Lactococcus lactis WS18, Lactococcus lactis subsp. Lactis TBRC 375, Levilactobacillus brevis TRBC 3003, and Pedicoccus pentosaceus WS11) with 150 g/L of papaya and 8 % sugar. Optimized PWK exhibited high phenolic (33.47 ± 0.26 μg GA/mL), flavonoid (15.58 ± 1.45 μg QE/mL), and glucosinolate (2.06 ± 0.17 mg RS/mL) contents, contributing to strong antioxidant activity (74.90 ± 0.47 %). PWK demonstrated potent antibacterial effects against Escherichia coli, Staphylococcus aureus, Bacillus cereus and Salmonella sp., with inhibition zones of 2.67 ± 0.58 mm, 3.07 ± 0.90 mm, 2.67 ± 0.58 mm, and 2.33 ± 1.15 mm, respectively, which were significantly higher than the nonprobiotic PWK variant (NP). PWK induced apoptosis in cancer cells through mitochondrial membrane potential reduction, with IC50 values of 20.96 mg/mL (MCF-7) and 23.15 mg/mL (HCT116) over 72 h. However, its high alcohol content remains a limitation, necessitating further optimization for broader consumer acceptance. Overall, PWK, which combines the nutritional benefits of papaya with health-promoting probiotics, presents itself as a promising functional beverage for supporting cancer prevention and overall well-being.